2019
DOI: 10.1016/j.aquatox.2019.105310
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to a chemical pesticide increases vulnerability to a biopesticide: Effects on direct mortality and mortality by predation

Abstract: Pesticide mixtures are increasingly used to fight pest species that developed resistance to pesticides. To assess the pesticide control efficiency and to reduce ecological damage to nontarget species, it is important to quantify the effect of these mixtures and compare them with the effect of their single pesticides on pest species, non-target species and their predator-prey interactions. We studied the effects of the chemical pesticide chlorpyrifos (CPF), the biopesticide Bacillus thuringiensis israelensis (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 99 publications
0
11
0
1
Order By: Relevance
“…This organophosphate pesticide is used worldwide (although has recently been banned or restricted to use in some countries), and has a higher lethal effect on aquatic animals at higher temperatures. We expected the heat spike to magnify the toxicity of the pesticide (CITS, ,, ), and the pesticide to reduce the heat tolerance (TICS, ,, ). Recent studies showed strong delayed mortality in mosquito larvae after exposure to heat extremes, but much less after exposure to the pesticide chlorpyrifos, suggesting a more rapid action of chlorpyrifos, and/or a longer toxicodynamic recovery after a heat spike. We therefore expected the toxicity of the pesticide to be more magnified when preceded than when followed by the heat spike.…”
Section: Introductionmentioning
confidence: 99%
“…This organophosphate pesticide is used worldwide (although has recently been banned or restricted to use in some countries), and has a higher lethal effect on aquatic animals at higher temperatures. We expected the heat spike to magnify the toxicity of the pesticide (CITS, ,, ), and the pesticide to reduce the heat tolerance (TICS, ,, ). Recent studies showed strong delayed mortality in mosquito larvae after exposure to heat extremes, but much less after exposure to the pesticide chlorpyrifos, suggesting a more rapid action of chlorpyrifos, and/or a longer toxicodynamic recovery after a heat spike. We therefore expected the toxicity of the pesticide to be more magnified when preceded than when followed by the heat spike.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is growing evidence of high activity of botanicals against mosquitos with no effects or even stimulatory effects on aquatic predators of mosquito larvae . In contrast, other categories of biorational insecticides can cause adverse effects on non‐target aquatic organisms . Curiously, recent studies indicate that aquatic predators exposed to sublethal doses of Bacillus thuringiensis var israelensis (Bt i ) are more successful predators after exposure …”
Section: Unintended Effects Of Biorational Insecticidesmentioning
confidence: 99%
“…For example, significantly more resistant C. pipiens larvae were consumed by Plea minutissima and Hyrdometra stagnorum but not Sigara lateralis than susceptible ones (Berticat et al, 2004 ). Furthermore, P. minutissima consumed more resistant than susceptible Bti-exposed Culex quinquefasciatus larvae (Delnat et al, 2019 ). These data show that the general cost of the resistance mechanism reduces the energy available for other life processes, making resistant individuals more accessible to predators.…”
Section: Methodsmentioning
confidence: 99%